PERENCANAAN KONFIGURASI JARINGAN KOMUNIKASI LTR EF. JOHNSON - Amir, Ardi (MEKTEK, 2006)
System of Communications of Radio Trunking exploiting system of Logic Trunked Radio where providing communications system make a move the goodness in one way, and also communications system two direction with the operating system of conventional and Trunking System.Use of system LTR for the communications of land enviroment of Airport can lessen the frequency use, so that do not bother the system of communications navigasi in airport.